USP10 is a potential mediator for vagus nerve stimulation to alleviate neuroinflammation in ischaemic stroke by inhibiting NF-κB signalling pathway - Xie, Chenchen; Gao, Xiang; Liu, Gang; Tang, Hao; Li, Changqing (Frontiers in Immunology, 2023)
Background: Vagus nerve stimulation (VNS) has a protective effect on neurological recovery in ischaemic stroke. However, its underlying mechanism needs further exploration. Ubiquitin-specific protease 10 (USP10), a member of the ubiquitin-specific protease family, has been shown to inhibit the activation of the NF-κB signalling pathway. Therefore, this study investigated whether USP10 acts as a key role in the protective effect of VNS against ischemic stroke and its mechanism. Methods: Ischaemic stroke model was constructed by transient middle cerebral artery occlusion (tMCAO) in mice. VNS was performed at 30 min, 24h, and 48h after the establishment of tMCAO. LV-shUSP10 was used to establish animal models with low expression of USP10 by the stereotaxic injection technique. USP10 expression induced by VNS after tMCAO was measured. The effect of VNS on neurological deficits, cerebral infarct volume, NF-κB pathway activation, glial cell activation, and release of pro-inflammation cytokines were assessed with or without USP10 silencing. Results: VNS enhanced the expression of USP10 in the cortex following tMCAO. VNS ameliorated neurological deficits and reduced cerebral infarct volume, but this effect was abrogated by the silence of USP10. The activation of the NF-κB pathway and the expression of inflammatory cytokines induced by tMCAO were suppressed by VNS. Moreover, it promoted the M1-to-M2 polarization in microglia and inhibited the activation of astrocytes. The silencing of USP10 obstructed the neuroprotective and anti-neuroinflammatory effects of VNS. Conclusion: USP10 is a potential mediator for VNS to alleviate neurological deficits, neuroinflammation, and glial cell activation in ischaemic stroke by the inhibition of NF-κB signalling pathway.